Synthesize of heterostructure TiO2 by simultaneous doping of double silver and phosphate to degradation of methylene blue under visible light - Zohre Moeini; Mohammad Hoseini; Mansooreh Dehghani; Mohammadreza Samaei; Saeed Jafari; Mahmoud Taghavi; Abooalfazl Azhdarpoor (Applied Water Science, 2024)
Abstract Photocatalysts show great potential as compounds for restoring contaminated water and wastewater resources. The study aims to synthesize a composite with high photocatalytic potential under visible light to photodegrade the organic pollutants. Ag/Ag3PO4@ TiO2 were synthesized by doping Ag and Ag3PO4 on TiO2. The composite was characterized using X-ray diffraction analysis (XRD), diffuse reflectance spectroscopy, Field emission scanning electron microscopy, and Energy-dispersive X-ray spectroscopy analyses, and its photodegradation ability was investigated by methylene blue. Utilization of pure TiO2 yielded a removal efficiency that was merely half of the efficiency achieved when using modified particles, owing to the reduction of TiO2 s band gap from 3.2 to 1.94 eV. In addition to its enhanced photocatalytic performance under visible light, the synthesized Ag/Ag3PO4@TiO2 photocatalyst demonstrated remarkable efficiency in removing dyes such as methylene blue from aqueous solutions. The removal efficiency at pH less than 7 in 50 ppm methylene blue solution using 3 g/l photocatalyst over 45 min visible light irradiation was approximately 90 percent. Under sunlight, photocatalytic reactions exhibited an efficiency of over 95 percent within 45 min. It can be concluded that the simultaneous introduction of metallic (Ag) and nonmetallic (PO4 3−) dopants significantly increases the efficiency of electron–hole recombination suppression in the photocatalyst and also decreases the band gap.